Effects of the Anterolateral Ligament and Anterior Cruciate Ligament on Knee Joint Mechanics: A Biomechanical Study Using Computational Modeling. Issue 4 (5th April 2022) - Kang, Kyoung-Tak; Koh, Yong-Gon; Park, Kyoung-Mi; Choi, Chong-Hyuk; Jung, Min; Cho, Hyunik; Kim, Sung-Hwan
Background: Recent studies on lateral knee anatomy have reported the presence of a true ligament structure, the anterolateral ligament (ALL), in the anterolateral region of the knee joint. However, its biomechanical effects have not been fully elucidated. Purpose: To investigate, by using computer simulation, the association between the ALL and anterior cruciate ligament (ACL) under dynamic loading conditions. Study Design: Descriptive laboratory study; Level of evidence, 5. Methods: The authors combined medical imaging from 5 healthy participants with motion capture to create participant-specific knee models that simulated the entire 12 degrees of freedom of tibiofemoral (TF) and patellofemoral (PF) joint behaviors. These dynamic computational models were validated using electromyographic data, muscle activation data, and data from previous experimental studies. Forces exerted on the ALL with ACL deficiency and on the ACL with ALL deficiency, as well as TF and PF contact forces with deficiencies of the ACL, ALL, and the entire ligament structure, were evaluated under gait and squat loading. A single gait cycle and squat cycle were divided into 11 time points (periods 0.0-1.0). Simulated ligament forces and contact forces were compared using nonparametric repeated-measures Friedman tests. Results: Force exerted on the ALL significantly increased with ACL deficiency under both gait- and squat-loading conditions. With ACL deficiency, the mean force on the ALL increased by 129.7% under gait loading in the 0.4 period ( P < .05) and increased by 189% under high flexion during the entire cycle of squat loading ( P < .05). A similar trend of significantly increased force on the ACL was observed with ALL deficiency. Contact forces on the TF and PF joints with deficiencies of the ACL, ALL, and entire ligament structure showed a complicated pattern. However, contact force exerted on TF and PF joints with respect to deficiencies of ACL and ALL significantly increased under both gait- and squat-loading conditions. Conclusion: The results of this computer simulation study indicate that the ACL and the ALL of the lateral knee joint act as secondary stabilizers to each other under dynamic load conditions.